2006
DOI: 10.1111/j.1551-2916.2006.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thickness on Piezoelectric Properties of Highly Oriented Lead Zirconate Titanate Films

Abstract: Lead zirconate titanate (PZT) films were deposited on platinized silicon substrates by spin coating using PZT sols containing polyvinylpyrrolidone (PVP) as an additive. PZT films with a 60/40 composition and a thickness of up to 8 μm were fabricated by repeating the deposition process 15 times on highly oriented (100) and (111) seed layers with the same composition. The films grew well in the direction of the seed layers and had a uniform and smooth surface without any cracks. As the thickness of the films inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Our results show that the reduction of the film thickness from ∼50 to ∼20 nm in both pure and Ca-modified is accompanied by a decrease of the d 33 eff values, which is in agreement with the tendency already observed in similar thicker polycrystalline ferroelectric films, with values in the range of 0.5 to 8 m. 39,40 One of the possible factors causing this reduction of the piezoelectric activity may be the increase of the residual stress with the decrease of the film thickness. 6 and 7) on those grains showing the highest out-of-plane piezoresponse values.…”
Section: Resultssupporting
confidence: 92%
“…Our results show that the reduction of the film thickness from ∼50 to ∼20 nm in both pure and Ca-modified is accompanied by a decrease of the d 33 eff values, which is in agreement with the tendency already observed in similar thicker polycrystalline ferroelectric films, with values in the range of 0.5 to 8 m. 39,40 One of the possible factors causing this reduction of the piezoelectric activity may be the increase of the residual stress with the decrease of the film thickness. 6 and 7) on those grains showing the highest out-of-plane piezoresponse values.…”
Section: Resultssupporting
confidence: 92%
“…In principle, however, this mechanism may be more generally applicable to other systems where the single crystal composition can be formed by reaction synthesis of two compositionally distinct phases. An important proviso is the suppression of multiple nucleation, which potentially could be achieved by top seeding with a single crystal and controlling the growth temperature. In terms of technological importance, ferroelectric and relaxor materials are clearly good candidates for further exploration of this crystal synthesis route.…”
Section: Discussionmentioning
confidence: 99%
“…16 Some studies have reported the improved properties of thin films with increasing film thickness, but only up to 10 mm. [17][18][19] Lebedev and Akedo 20 also reported the improved properties of thicker PZT films with thicknesses up to 60 mm fabricated by AD process.…”
Section: Introductionmentioning
confidence: 95%
“…The interface clamping effect is usually decreased with increasing film thickness, thereby easing the domain movement and improving the electric properties 16 . Some studies have reported the improved properties of thin films with increasing film thickness, but only up to 10 μm 17–19 . Lebedev and Akedo 20 also reported the improved properties of thicker PZT films with thicknesses up to 60 μm fabricated by AD process.…”
Section: Introductionmentioning
confidence: 99%